Mechanical Atherothrombectomy (MATH) in the Treatment of Chronic Occlusions of the Popliteal Artery - Bulvas, Miroslav (Cardiology and Cardiovascular Medicine, 2019)
Mechanical atherothrombectomy (MATH) is rapid, effective and safe technique used for endovascular removal of occlusive material from peripheral vessels. It is widely used in patients with acute and subacute lower limb ischemia. Efficacy of the Rotarex catheter depends on the presence of fragmentable occlusive material and the treatment is successful also in patients with chronic ischemic symptoms. The technique reduces vessel barotrauma by lowering the frequency of balloon angioplasties and stenting procedures. Additionally, the need for surgical treatment can be also lowered. The purpose of this review is to present an illustrative series of patients with popliteal artery occlusions and chronic ischemic symptoms, that may help the reader to learn about the technique potential in this challenging vascular location.